Environmental Justice and Islamic Ethics: A Conversation with Anna M. Gade - Hanifah, Laila (MAARIF Institute, 2024)
Growing up in California, the land of mountains and wilderness, Anna M. Gade was deeply connected to the landscapes of her hometown. While environmental studies have traditionally been rooted in the hard sciences, she charted a unique path by focusing her attention on the humanities within environmental studies. Specifically, by incorporating Islamic perspectives, she challenges and enriches conventional understandings of the environment and environmental humanities. As Vilas Distinguished Achievement Professor at the Gaylord Nelson Institute for Environmental Studies at the University of Wisconsin-Madison, USA, Prof. Gade is a leading voice in this innovative field. She is the author of Muslim Environmentalisms: Religious and Social Foundations (Columbia University Press, 2019), a pivotal work exploring the intersections of faith and ecology. Beyond her academic contributions in the United States, Prof. Gade’s global impact includes serving as a visiting professor at Universitas Gadjah Mada and Universitas Islam Internasional Indonesia (UIII). Her efforts bridge cultural and academic boundaries, advancing a richer understanding of environmental stewardship from a Muslim perspective.